Current Situation of Mycotoxin Contamination and Co-occurrence in Animal Feed—Focus on Europe - Isabelle P. Oswald; Olivier Puel; Iuliana Aprodu; Cristina Tabuc; Anca Nicolau; Daniela Marin; Ionelia Taranu; Panagiotis Tassis; Eleni Tzika; Gerd Schatzmayr; Elisabeth Streit (Toxins, 2012)
Mycotoxins are secondary metabolites produced by fungi especially those belonging to the genus Aspergillus, Penicillum and Fusarium. Mycotoxin contamination can occur in all agricultural commodities in the field and/or during storage, if conditions are favourable to fungal growth. Regarding animal feed, five mycotoxins (aflatoxins, deoxynivalenol, zearalenone, fumonisins and ochratoxin A) are covered by EU legislation (regulation or recommendation). Transgressions of these limits are rarely observed in official monitoring programs. However, low level contamination by Fusarium toxins is very common (e.g., deoxynivalenol (DON) is typically found in more than 50% of the samples) and co-contamination is frequently observed. Multi-mycotoxin studies reported 75%–100% of the samples to contain more than one mycotoxin which could impact animal health at already low doses. Co-occurrence of mycotoxins is likely to arise for at least three different reasons (i) most fungi are able to simultaneously produce a number of mycotoxins, (ii) commodities can be contaminated by several fungi, and (iii) completed feed is made from various commodities. In the present paper, we reviewed the data published since 2004 concerning the contamination of animal feed with single or combinations of mycotoxins  and highlighted the occurrence of these co-contaminations.